The Effect of Cognitive Rehabilitation on Balance Skills of Individuals with Multiple Sclerosis. Issue 1 (2nd January 2021) - Azimian, Mojtaba; Yaghoubi, Zahra; Ahmadi Kahjoogh, Mina; Akbarfahimi, Nazila; Haghgoo, Hojjat Allah; Vahedi, Mohsen
Abstract: Balance skills can be affected by slow information processing speed in people with multiple sclerosis. This study explored the effect of cognitive-based rehabilitation on balance skills of individuals with multiple sclerosis. Seventy-one participants with multiple sclerosis were randomly assigned to the usual occupational therapy exercises as a control group (n = 36, male = 10) or the cognitive rehabilitation group (n = 35, male = 10). Using several assessments pre-intervention, post-intervention and two months after completion, participants in the cognitive rehabilitation group showed significant improvement in their balance skills in post-test and as well as follow-up measurements compared to the control group. Results also showed a large effect of cognitive rehabilitation for balance (eta-squared= 0.59) and for information processing speed measured. Inclusion of tasks related to information processing speed to the usual occupational therapy exercises seemed to be able to improve the balance skills of people with multiple sclerosis.